Innovative Methods of Learning Foreign Languages and Lifelong Learning on Sustainable Development - Paskhal, Oleksandra; Vlasiuk, Iryna; Turchynova, Ganna; Zaskalieta, Svitlana; Vasylchenko, Olena (European Journal of Sustainable Development, 2025)
Innovative approaches to developing foreign language competence are closely related in the context of globalisation and education in digital transformation. Interactive methods, digital technologies, blended learning, etc., are used to enhance language learning effectiveness and make the learning process adapt to the requirements of the students. Firstly, the study aims to analyse modern innovative approaches to teaching foreign languages in the conditions of lifelong learning and to estimate their effectiveness for diverse age and professional groups. The research methodology is grounded on the analytical processing of scientific sources, statistical data, and results of the respondents’ survey, which is aimed at assessing digital technologies’ effect on the progress of foreign language competence development. The results suggest that blended learning, mobile applications, online courses, and project-structured strategies are the most effective. At the same time, the technologies of gamification and VR/AR are ineffective because of the technical barriers. Results of the analysis indicated that the effectiveness of the methods depends on the level of their training and their occupational professional practice. Young professionals also exhibit higher motivations to utilise digital resources as compared to experienced professionals. However, the latter group prefers to use personal learning programmes. The practical significance of the study is to formulate recommendations for introducing innovative approaches to foreign language training in the continuing education system, which will increase the competitiveness of specialists in the international labour market. Keywords: foreign language competence, continuing education, digital technologies, blended learning, innovative methods, communicative approach, gamification, project-based learning, CLIL, artificial intelligence, sustainable lifestyles.